(untitled) (Physical Culture and Sport: Scientific Perspective, 2024)
The purpose of this study was to theoretically substantiate, develop and experimentally test the methodology of teaching orienteering to senior pupils in the process of physical education. Material and Methods. Internet platforms Scopus, Web of Science, PubMed were used to select articles for the analysis of experimental systems of physical education lessons for senior pupils with sports-oriented training and injury prevention. The preference was for publications in the categories for 2018-2023. The articles selected in this way were used to analyse sports orientation and injury prevention during training. The technologies had to meet the following criteria: effectiveness, ease of use, and accessibility. Results. As a result of the search of literary sources on the topic of prevention of injuries 1010 sources were selected by the keyword ‘injury’, from which then by refinements by keywords ‘sports integration’, ‘prevention’, ‘sports orientation’ 210 sources were selected, from which 5 sources were found for analysis. Of these sources, 3 describe the problems of injuries in schools and methods of their prediction, 3 sources explain the models of sports orientation and high school.Conclusions. An important role in physical education is given to increasing motivation for regular exercise, so physical education of students needs constant modernisation, both in terms of content and technology. A creative approach to injury prevention involves a deep understanding of the medical and biological basis of the training process. This encourages students to master the basics of anatomy, physiology, biochemistry, and biomechanics. The data obtained in the articles expand the knowledge of sports-oriented physical education of students and allow them to be recommended in other educational institutions to improve the level of physical fitness and prevent injuries among young people.